One-minute integrated rainfall rate statistics from a rain gauge network in Colombia: Accuracy of prediction methods (2020)
Reliable rainfall rate complementary cumulative distributions are critical for the design of microwave communications systems operating above around 8 GHz. This Letter presents the results of the analysis of more than 5 years of 1-minute integrated rainfall accumulation data for 12 stations. This new dataset will prove useful considering the sharing analyses that must be executed for IMT services in the 24.25–27.5, 37–43.5, 45.5–47, 47.2–48.2 and 66–71 GHz spectrum bands. The resulting statistics can complement the entries in the database of ITU-R Study Group 3 for the region.